Fourier transform infrared spectroscopy study of the effect of pH on anion and cation adsorption onto poly(acryloamidino diethylenediamine) - Ko, YG; Choi, US; Park, YS; Woo, JW (WILEY, 2004)
The role of hydrogen bonding in the chemistry of transition-metal complexes remains a topic of intense scientific and technological interest. Poly(acryloamidino diethylenediamine) was synthesized to study the effects of hydrogen bonding on complexes at different pHs. The polymer was synthesized through the coupling of diethylene triamine with polyacrylonitrile fiber in the presence of AlCl3 . 6H(2)O addition. The adsorption capacity of this polymer was 11.4 mequiv/g. The ions used for the adsorption test were CrO42-, PO43-, Cu2+, Ni2+, Fe2+, and Ag+. All experiments were confirmed with Fourier transform infrared. In the study of anion adsorption, at low pHs, only ionic bonds existed, whereas at high pHs, no bonds existed. However, in the middle pH region, both ionic bonds and hydrogen bonds formed between poly(acryloamidino diethylenediamine) and the chromate ion or phosphate ion. When poly(acryloamidino diethylenediamine) and metal ions (Cu2+, Ni2+, Fe", and Ag+) formed complexes, a hydrogen-bonding effect was not observed with Fourier transform infrared. The quantity of metal ions adsorbed onto poly(acrylo-amidino diethylenediamine) followed the order Ag+ > Cu2+ > Fe2+ > Ni2+. (C) 2004 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem 42: 2010-2018, 2004.